2006
DOI: 10.1007/s00125-006-0365-6
|View full text |Cite
|
Sign up to set email alerts
|

Reg (regenerating) gene overexpression in islets from non-obese diabetic mice with accelerated diabetes: role of IFNβ

Abstract: Aims/hypothesis The expression of IFNβ in beta cells results in accelerated type 1 diabetes. The REG family of beta cell proliferation factors have been described as autoantigens in autoimmune diabetes. The aim of this study was to determine the effect of IFNβ on Reg expression, and the implications of this in terms of autoimmunity. Methods Reg gene expression was determined in islets from non-obese diabetic (NOD) RIP-HuIFNβ mice by cDNA microarray, quantitative real-time PCR and immunohistochemistry. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…These results support the idea that REG Iα mRNA over-expression is associated with inflammation triggered by autoimmune disorders such as SS. It was reported that Reg gene expression was regulated by several factors, such as nicotinamide [18,19], glucocorticoids [18,20], nutrient factors [21], IL-6 [12,18], IL-8 [22], IL-11 [23], IL-22 [24], IFN-γ [25], IFN-β [12] and CINC-2β [26]. Among the major inflammatory mediators involved in the induction of inflammation of the salivary glands with primary SS, IL-6 is an important proinflammatory cytokine in relation to lymphocyte infiltration [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results support the idea that REG Iα mRNA over-expression is associated with inflammation triggered by autoimmune disorders such as SS. It was reported that Reg gene expression was regulated by several factors, such as nicotinamide [18,19], glucocorticoids [18,20], nutrient factors [21], IL-6 [12,18], IL-8 [22], IL-11 [23], IL-22 [24], IFN-γ [25], IFN-β [12] and CINC-2β [26]. Among the major inflammatory mediators involved in the induction of inflammation of the salivary glands with primary SS, IL-6 is an important proinflammatory cytokine in relation to lymphocyte infiltration [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-8 are reported to induce REG Iα mRNA in vitro [18,21,22] and in vivo [39], and IL-11 [23], IL-22 [24], IFN-γ [25], IFN-β [12] and CINC-2β [26] are also reported to induce REG Iα mRNA. IL-6R and gp130 are known as signal transducers of IL-6.…”
Section: Cytokine/chemokine(s) Gene Expression In Msgmentioning
confidence: 97%
See 2 more Smart Citations
“…The specificity of the overexpression of Reg2 in the diabetogenic process was reinforced by the fact that it was also observed in NOD male mice after treatment with cyclophosphamide, whereas this drug has no effect in male control mice. Other stimuli for Reg2 expression related to T1D are diet (18), type 1 IFN (19), and insulin-like growth factor-1 (20) among others.…”
mentioning
confidence: 99%